Preservation of myocardial β-adrenergic receptor signaling delays the development of heart failure after myocardial infarction - White, David C. (The National Academy of Sciences, 2000)
When the heart fails, there is often a constellation of biochemical alterations of the β-adrenergic receptor (βAR) signaling system, leading to the loss of cardiac inotropic reserve. βAR down-regulation and functional uncoupling are mediated through enhanced activity of the βAR kinase (βARK1), the expression of which is increased in ischemic and failing myocardium. These changes are widely viewed as representing an adaptive mechanism, which protects the heart against chronic activation. In this study, we demonstrate, using in vivo intracoronary adenoviral-mediated gene delivery of a peptide inhibitor of βARK1 (βARKct), that the desensitization and down-regulation of βARs seen in the failing heart may actually be maladaptive. In a rabbit model of heart failure induced by myocardial infarction, which recapitulates the biochemical βAR abnormalities seen in human heart failure, delivery of the βARKct transgene at the time of myocardial infarction prevents the rise in βARK1 activity and expression and thereby maintains βAR density and signaling at normal levels. Rather than leading to deleterious effects, cardiac function is improved, and the development of heart failure is delayed. These results appear to challenge the notion that dampening of βAR signaling in the failing heart is protective, and they may lead to novel therapeutic strategies to treat heart disease via inhibition of βARK1 and preservation of myocardial βAR function.